Phenotype‐driven variant filtration strategy in exome sequencing toward a high diagnostic yield and identification of 85 novel variants in 400 patients with rare Mendelian disorders. Issue 8 (19th May 2021) - Marinakis, Nikolaos M.; Svingou, Maria; Veltra, Danai; Kekou, Kyriaki; Sofocleous, Christalena; Tilemis, Faidon‐Nikolaos; Kosma, Konstantina; Tsoutsou, Eirini; Fryssira, Helen; Traeger‐Synodinos, Joanne
Abstract: About 6000 to 7000 different rare disorders with suspected genetic etiologies have been described and almost 4500 causative gene(s) have been identified. The advent of next‐generation sequencing (NGS) technologies has revolutionized genomic research and diagnostics, representing a major advance in the identification of pathogenic genetic variations. This study presents a 3‐year experience from an academic genetics center, where 400 patients were referred for genetic analysis of disorders with unknown etiology. A phenotype‐driven proband‐only exome sequencing (ES) strategy was applied for the investigation of rare disorders, in the context of optimizing ES diagnostic yield and minimizing costs and time to definitive diagnosis. Overall molecular diagnostic yield reached 53% and characterized 243 pathogenic variants in 210 cases, 85 of which were novel and 148 known, contributing information to the community of disease and variant databases. ES provides an opportunity to resolve the genetic etiology of disorders and support appropriate medical management and genetic counseling. In cases with complex phenotypes, the identification of complex genotypes may contribute to more comprehensive clinical management. In the context of effective multidisciplinary collaboration between clinicians and laboratories, ES provides an efficient and appropriate tool for first‐tier genomic analysis.